Implementation of Environmental Device Monitoring Using Zabbix in the Pusat Data Sarana dan Informasi (PDSI) - Riyan Aji Nugroho; Perani Rosyani (CV. Multi Kreasi Media, 2023)
Pusat Data Sarana Informasi (PDSI) is that data management and information systems have a strategic role in supporting the implementation of policies in the field of communication and informatics in Indonesia. In this study, a system was designed to monitor the working environment of the device. This system uses Zabbix Server as a relatively inexpensive solution to save system manufacturing costs. By using this system, an administrator can monitor the existing environmental devices in the Data Center online. Through this monitoring, administrators can detect tampering or damage to the device and take appropriate action to fix it. Thus, this environment device monitoring system helps maintain the reliability and availability of the data center infrastructure.